Математичний аналіз процесу жарення - Назарова, Ольга Петрівна; Назарова, Ольга Петровна; Nazarova, Olha; Корощенко, М. Г. (Мелітополь: ТДАТУ, 2021)
UK: У статті розглянуто математичний опис процесу жарення. Це дозволяє більш точно дослідити об'єкт, дає можливість прогнозувати температурний режим і ступінь готовності об'єкта, який досліджується. EN: The article discusses the mathematical a description of the process of roasting. This allows you to more accurately examine the object, makes it possible to predict the temperature regime and the degree of readiness of the object that is being investigated.
Keywords: модель; жарення; компонент; параметри; model; roasting; component; parameter